Key studies that have changed the history and treatment of early HER2+ breast cancer: focus on individual therapy - I. V. Kolyadina; I. V. Poddubnaya (ABV-press, 2021)
HER2-positive breast cancer is a unique subtype of the disease, not only in terms of aggressive biology, but also in terms of treatment options. Over the past 15 years, the strategy for treating early HER2-positive breast cancer has undergone a real evolution - from the absence of anti-HER2 therapy to the sequential introduction of adjuvant, neoadjuvant and post neoadjuvant approaches. This review describes key studies of systemic therapy for HER2-positive breast cancer stage I-III, which made it possible to establish clear priorities in the sequence of surgical and systemic steps, identify high risk groups which need of escalation of treatment, and determine the optimal anti-HER2 therapy for each steps, as well as de-escalation of stage I treatment without losing its effectiveness. The news from the latest cancer conferences (SABCS, ESMO, ASCO) on the impact of various biological markers on the effectiveness of anti-HER2 agents is presented. A clear concept of modern treatment of early HER2-positive breast cancer has been formed, allowing individualized approaches, and achieving better results of the therapy this aggressive biological subtype.